2011
DOI: 10.1152/jn.00569.2010
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in task-specific modulation of anticipatory postural adjustments in individuals with spastic diplegic cerebral palsy

Abstract: We examined whether individuals with spastic diplegic cerebral palsy (SDCP) have the ability to utilize lower leg muscles in anticipatory postural adjustments (APAs) associated with voluntary arm movement while standing, as well as the ability to modulate APAs with changes in the degree of postural perturbation caused by arm movement. Seven individuals with spastic diplegia (SDCP group, 12-22 yr of age) and seven age- and sex-matched individuals without disability (control group) participated in this study. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
6
11
0
Order By: Relevance
“…This finding suggests that individuals with SDCP have the ability to modulate anticipatory activation of ventral postural muscles with changes in the degree of perturbation. This is a surprising finding, since our previous study on APAs in the load-lifting task revealed that insufficient modulation of anticipatory activation of postural muscles is a primary constraint on APAs while standing in individuals with SDCP (Tomita et al 2011). In addition, an inability to modulate postural muscle activities to fit task conditions in these individuals has been reported for voluntary forward reach while sitting (van der Heide et al 2004) and compensatory postural adjustments (CPAs) to backward translation of a support surface while standing (Roncesvalles et al 2002).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This finding suggests that individuals with SDCP have the ability to modulate anticipatory activation of ventral postural muscles with changes in the degree of perturbation. This is a surprising finding, since our previous study on APAs in the load-lifting task revealed that insufficient modulation of anticipatory activation of postural muscles is a primary constraint on APAs while standing in individuals with SDCP (Tomita et al 2011). In addition, an inability to modulate postural muscle activities to fit task conditions in these individuals has been reported for voluntary forward reach while sitting (van der Heide et al 2004) and compensatory postural adjustments (CPAs) to backward translation of a support surface while standing (Roncesvalles et al 2002).…”
Section: Discussionmentioning
confidence: 82%
“…This is a surprising finding, since our previous study on APAs in the load-lifting task revealed that insufficient modulation of anticipatory activation of postural muscles is a primary constraint on APAs while standing in individuals with SDCP (Tomita et al 2011). In addition, an inability to modulate postural muscle activities to fit task conditions in these individuals has been reported for voluntary forward reach while sitting (van der Heide et al 2004) and compensatory postural adjustments (CPAs) to backward translation of a support surface while standing (Roncesvalles et al 2002). Since the internally or externally induced postural perturbations in these previous studies are in the forward direction, activation of dorsal postural muscles is needed to maintain postural equilibrium.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations